ONLINE CLEARANCE SYSTEM - Adamu, A. (FUDMA JOURNAL OF SCIENCES, 2022)
Each year, many institutions churn out number of graduating student that must be cleared by different unit through a process called clearance. The traditional method of clearance involves student to physically visits clearance offices; student affairs, bursary, library, sports and registry department to get endorsed for clearance. The traditional method of clearance is time consuming, requires graduating student to physically visit various offices and some key staff may not be available at the time of visit and there is possibility of duplication or loss of data. Thus, the developed online clearance system overcomes the drawback to the traditional method of clearance. The online clearance system was developed using Windows 7 Operation System (OS) as development environment, MySQL for database design, Hypertext Pre-Processor (PHP) for the overall programming and Hypertext Mark-up Language (HTML) couple with Cascading Style Sheet (CSS) for the Graphical User Interface (GUI). A total of 150 student and 50 staff were used to evaluate the developed system for usability, convenience of service delivery and accessibility with 88.1%,89.8% and 95.3% cumulatively affirming that the system is usable, convenient in terms of service delivery and accessible in delivery effective and efficient clearance in a timely manner.
Keywords: Clearance; Graduating Student; Institution; Final Year